2022
DOI: 10.3399/bjgp.2021.0655
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing symptom appraisal and help-seeking of older adults with possible cancer: a mixed-methods systematic review

Abstract: Background: The burden of cancer falls predominantly on older adults. Prompt presentation to primary care with cancer symptoms could result in an earlier diagnosis. However patient appraisal and help seeking decisions involving cancer symptoms are complex and may be further complicated in older adults. Aim: To explore the effect of older age on patients’ appraisal of symptoms that may indicate cancer and their decision to seek help for these symptoms. Design: Mixed methods systematic review Method: Electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 105 publications
0
10
0
Order By: Relevance
“…Supporting this hypothesis, a recent systematic review found that self‐management of symptoms (e.g. watchful waiting or trying over the counter treatment before visiting the doctor) was a barrier to help‐seeking for cancer symptoms among older adults 24 …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Supporting this hypothesis, a recent systematic review found that self‐management of symptoms (e.g. watchful waiting or trying over the counter treatment before visiting the doctor) was a barrier to help‐seeking for cancer symptoms among older adults 24 …”
Section: Discussionmentioning
confidence: 98%
“…Our finding that older age was associated with increased likelihood of help-seeking and being comfortable to reconsult is also in line with the findings of the systematic review. 24 This has potential implications for younger peoples' experiences of help-seeking and reconsulting, particularly given the rise in incidence of early-onset cancers (i.e. cancers diagnosed in adults <50 years old).…”
Section: Comparison With Existing Researchmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 , 31 33 This may result in fewer proximal social cues (that is, everyday interpersonal interactions with friends, family, and colleagues) that help males to either recognise and understand the importance of their symptoms, or to seek help as a result of their concerns being legitimised and additional information being provided. 17 , 29 , 32 , 34 , 35 Overcoming cultural stigmas associated with prostate cancer and providing proximal social cues should, therefore, be a focus of future strategies for improving early presentation in Black males.…”
Section: Discussionmentioning
confidence: 99%
“…Existing co-morbidities or normal signs and symptoms of ageing may mask potential red flag symptoms of cancer, impairing both the patient’s and clinician’s recognition of these, thereby increasing time to referral [ 36 ]. For example, the eFI includes heart failure as a contributing factor to frailty [ 11 ].…”
Section: Discussionmentioning
confidence: 99%